The Symbolist Home and the Tragic Home. - Goodkin, Richard E. (John Benjamins Publishing Company, 1984)
Tragedy as Symbolism It is the symbolic nature of Oedipus' quest which most centrally links the notions of Tragedy and Symbolism in the Oedipus Tyrannus, and that under the aegis of the concepts of home and homing.